An accurate localization system for Nondestructive testing based on magnetic measurements in quasi-planar domain. (June 2019) - Cerro, G.; Ferrigno, L.; Laracca, M.; Milano, F.; Carbone, P.; Comuniello, A.; De Angelis, A.; Moschitta, A.
Highlights: Magnetic measurement system able to estimate the position of an ECT probe. Performance analysis of the proposed localization system. Mutual influence of ECT and Localization systems. Abstract: Localization of eddy current probes in Nondestructive Testing allows merging the defect detection with the information about defect positions. Typically, this task requires the usage of additional and costly position measurement systems or software assisted handlers in controlled laboratory conditions. However, many of these tests require free hand movements of the eddy current probes. In addition, in many industrial applications low cost is a stringent requirement. This paper proposes a novel solution to address the considered issues. In particular, the paper describes the usage of a magnetic 2D wireless localization method, able to track the probe position during the execution of Nondestructive Tests. To the best of our knowledge, such approach is novel and promises to provide localization information in Nondestructive Testing by means of low-cost hardware. Moreover, it is characterized by a light computational burden, since it reuses most of the equipment already needed for the test itself. Preliminary results, proving the suitability of a real time simultaneous testing and localization system, are reported in this paper.